LINC00957 Acted as Prognostic Marker Was Associated With Fluorouracil Resistance in Human Colorectal Cancer - Zhang, Li Hua; Li, Long Hai; Zhang, Peng Fei; Cai, Yan Fei; Hua, Dong (Frontiers in Oncology, 2019)
Colorectal cancer (CRC) remains one of the most prevalent gastrointestinal tract malignancies in China. Accumulating evidence indicates that long intergenic non-coding RNAs (lincRNAs) play a crucial role in predicting survival of patients with CRC. However, the clinical significance of novel lincRNA, LINC00957 in CRC remains to be elucidated. Therefore, the present study aimed to investigate the expression profile and clinical significance of LINC00957 expression in CRC tumor tissues. Furthermore, the potential molecular mechanism underlying the aberrant expression of LINC00957 in CRC was also assessed. Using quantitative real-time PCR (qRT-PCR), the expression levels of LINC00957 in CRC tumor tissues and cell lines were analyzed. The findings revealed that expression of LINC00957 was significantly higher in CRC tumor tissues compared to paired normal tissues. In addition, the expression of LINC00957 was significantly correlated with advanced TNM stage and chemotherapy outcome; however, no significant association was found with age, gender, tumor size, histological grade, and primary tumor location. CRC patients with high LINC00957 expression exhibited significant poor overall survival (P=0.002). Multivariate survival analysis indicated that expression of LINC00957 was a significant independent prognostic factor for CRC (P=0.010). Mechanistically, inhibition of LINC00957 expression reversed 5-FU resistance through down-regulation of P-gP expression. In conclusion, the findings of the present study indicated that LINC00957 plays a promoting role in the malignant progression and development of chemo-resistance in patients with CRC. Thus, LINC00957 expression signature might serve as a novel prognostic biomarker and potential therapeutic targets for CRC.